Respuesta :
Answer:
33
Step-by-step explanation:
1. Let's solve for g(3)
Step 1: Plug in the value of x.
- [tex]g(3)=3(3)-2[/tex]
Step 2: Simplify.
- [tex]g(3)=9-2[/tex]
- [tex]g(3)=7[/tex]
2. Let's solve for g(-8)
Step 1: Plug in the value of x.
- [tex]g(-8) = 3(-8)-2[/tex]
Step 2: Simplify.
- [tex]g(-8) = -24 - 2[/tex]
- [tex]g(-8)=-26[/tex]
3. Now, let's subtract g(-8) from g(3).
- [tex]g(3)-g(-8)[/tex]
- [tex](7)-(-26)[/tex]
- [tex]7+26[/tex]
- [tex]33[/tex]
Therefore, the answer is 33.
Answer:
33
Step-by-step explanation:
g(x) = 3x - 2
g(3) = when x of g(x) function is 3.
g(3) = 3(3) - 2
g(3) = 9 - 2
g(3) = 7
g(-8) = 3(-8) - 2
g(-8) = -24 - 2
g(-8) = -26
g(3) - g(-8)
7 - (-26) = 33